Astragalin flavonoid inhibits proliferation in human lung carcinoma cells mediated via induction of caspase-dependent intrinsic pathway, ROS production, cell migration and invasion inhibition and targeting JAK/STAT signalling pathway - Xu, Guoxing; Yu, Biqing; Wang, Rujuan; Jiang, Jie; Wen, Fangjing; Shi, Xiaowu (Cellular and Molecular Biology, 2021)
The aim of the current study was to investigate the anti-lung cancer effects of astragalin. Studies were also undertaken to evaluate its effects on apoptosis induction, ROS production, cellular migration and invasion and JAK/STAT3 signalling pathway. MTT assay was used to evaluate cell viability in NSCLC A549 cells after exposure to astragalin molecule. Apoptosis was investigated using AO/EB staining, comet assay and western blotting assay. Fluorescence microscopy was implemented to estimate ROS production. Cell migration and invasion were measured using transwell chambers assay. Effects of astragalin on JAK/STAT pathway were investigated using western blotting assay. Results showed astragalin molecule induced inhibition of proliferation in A549 cells in a dose-dependent fashion. Further, the antiproliferative effects were found to mediate via apoptosis as suggested by AO/EB staining and western blotting assay. Astragalin modulated the expressions of caspase-3, caspase-9, Bax, Bak, Cyt-c Bcl-2, XIAP and Bcl-xL. Astragalin induced DNA damage in A549 cells which too indicated apoptotic cell death. Astragalin molecule enhanced the production of ROS by A549 cells. It inhibited both cell migration and invasion of A549 cells in a concentration-dependent manner. Finally, astragalin drug was observed with remarkable potential of targeting JAK/STAT pathway in A549 NSCLC cells. These results indicated that astragalin drug could prove helpful in lung cancer treatment and research provided more in-vivo studies are performed.